Healing a divided nation : land rights, an Aboriginal perspective - Jacobs, Cedric, 1943- (Bullsbrook, W.A. : Veritas Publishing Company, 1986)
Highlights need for Christian solution to land rights issues; criticizes roles of DAA, ADC and handing over of Ayers Rock; states policy of Goldfields and Western Desert Christian Aboriginal Movement; includes biographical notes on author.
Bibliography: p. 70-72.
Keywords: Aboriginal Australians -- Land tenure; Religions - Christianity; Politics and Government - Political action - Land rights; Western Desert (WA SF51, SF52, SG51, SG52); Uluru / Ayers Rock (South Central NT SG52-08)